Have a Free Video Meeting with one of our friendly tutors.

To differentiate an equation, the first step is multiplying the coefficients of the variables (the coefficient is the number a variable is already being multiplied by, for example in 6x the coefficient of...

Disguised quadratic. Let y=x^2So quadratic become y^2-4y-5=0so (y-5)(y+1)=0so y=5 and y=-1so x^2 = 5 or -1cannot be -1 as not real henso x^2=5x=+-sqrt(5)

Write 3^(t) as an expression involving x : We can rewrite x = 3^(-t) + 1 as x - 1 = 3^(-t) ; equivalently, 3^(t) = (x-1)^(-1). Substitute this expression into y, to write y in terms of x: y = 2 x 3^(t) = ...

If you draw a circle with radius one, centre origin, draw a right angled triangle within the circle in the top right quadrant, so that the hypotenuse is also a radius of the circle, label the angle clockw...

2x + 5 lnx